Controls on hydrocarbon column-heights in the Eastern province of Haltenbanken, the Norwegian Sea - Atakan, Karoline Aylin (The University of Bergen, 2016)
Knowledge of controls on hydrocarbon column-heights is highly relevant in hydrocarbon exploration, and important for determination of in-place volumes of prospects. The eastern province of Haltenbanken in the Norwegian Sea constitutes a normally- to hydrostatic pressured region, and is host to several large oil and gas fields as well as minor discoveries. This study aims to investigate the controls on the hydrocarbon column-heights and the distribution of hydrocarbons in the area. Regional seismic interpretation of the main reservoir units in the area, the Fangst and Båt Groups, has been conducted on the basis of 3-D seismic and published well data. Investigation and mapping of fluid contact locations relative to spill points allowed for distinguishing between filled and underfilled structures. Seismic amplitude variations in the overburden above the Jurassic reservoirs were investigated to identify potential areas of leakage. Results from the 15 investigated structures in the study area can give the following categorization: 1) fluid contacts coinciding with spill point, 2) fluid contacts that do not coincide with spill point and 3) structures where it was not possible to determine the controlling factors. Nine structures have fluid contacts coinciding with spill point, and are suggested to be filled. The location of spill point is suggested to be the controlling factor on the column-height in these structures. One structure is suggested to be underfilled, and in one of the structures the uppermost reservoir level is suggested to be underfilled while deeper reservoir levels are likely filled. The column-heights in the reportedly underfilled reservoirs are suggested to be controlled by vertical leakage. In one of the structures the fluid contact is located deeper than spill point, and the column-height is suggested to be controlled by fault sealing and/or leakage through the seal. The controlling factor on hydrocarbon column-heights in the remaining four structures remains unclear, as it has not been possible to ...